Nested Spontaneous Symmetry Breakings of Light in Kerr Ring Resonators - Hill, Lewis; Del Haye, Pascal; Oppo, Gian Luca (Optics InfoBase Conference Papers, 2022)
We show multiple nested spontaneous symmetry breakings in a ring resonator with two counter-propagating light waves. The results could be of interest for telecom systems, nonlinear polarization control, soliton frequency combs, and all-optical oscillators.
CRIS-Team Scopus Importer:2022-09-09